STRUCTURE SOLUTIONS FOR THE CONSTRUCTION AND REPAIR OF FOUNDATIONS ON LOESS SOILS IN SEISMIC ZONES - Eshnazarovich, Berdimurodov Abdiqayum (PT. Antis International Publisher, 2024)
When repairing slate floors and foundations in earthquake areas, we propose to carry out the expansion of the base surface of the foundation in practice using two methods. In addition there are various methods related to the repair of slate floors and foundations used in construction practice, which can be conditionally divided into three types, depending on the general purpose: reducing the value of the pressure transmitted to the slate floor; strengthening the foundation material; increasing the strength indicators of the slate grout. The Lewis sinks and the strength of the foundation drops sharply. In this case, a loss of stability of the base is observed, which often leads to the complete or partial destruction of buildings and structures. Let's also consider ways to prevent this.